Optimization and experimental study of the auxiliary mechanism for organic fertilizer side throwing - Liu, Hongxin; Xie, Yongtao; Zhao, Yijian; Shang, Jiajie (International Journal of Agricultural and Biological Engineering, 2025)
To correct the working state of a throwing component and achieve an ideal narrow, far, and uniform material projectile flow for a side-throwing device for organic fertilizer with inclined opposing discs, a systematic optimization of the auxiliary mechanisms (baffle, upper deflector, and side deflector) was performed. Starting from a basic analysis of the working principles of each side-throwing device component, theoretical modeling and MATLAB numerical calculations were used to determine the departure angle providing the farthest fertilizer distance, as well as the maximum and minimum throwing angles required to achieve a target distance of 10 m. These calculations informed the optimization and configuration of the basic structures of each auxiliary mechanism component. The impact of the baffle on fertilizer movement was analyzed, leading to an optimization of the baffle’s height and its horizontal position in relation to the main throwing disc, guiding the design of the discharge port structure. Combining the theoretical analysis results, the surface of the upper deflector was fitted, and a side deflector was added to assist in limiting the scattering angle of the projectile flow. An EDEM simulation showed that the optimized auxiliary mechanisms worked well together, resulting in a narrower discharge width, a more concentrated projectile flow, and improved uniformity in spreading. Prototype testing confirmed that from the side projection angle between the spreading direction and vertically upward, the projectile flow angle domain was adjusted from 18°-45° to 23°-32°. With the optimization of other auxiliary mechanisms, the coefficient of variation in spreading uniformity decreased from 25.95% to 19.21%, the effective throwing distance increased from 10.1 to 11.2 m, and the scattering angle decreased from 12° to 4°, effectively enhancing the performance of the side-throwing device. Keywords: organic fertilizer side throwing, auxiliary mechanism, optimization research, virtual simulation, experiment DOI: 10.25165/j.ijabe.20251804.9168 Citation: Liu H X, Xie Y T, Zhao Y J, Shang J J. Optimization and experimental study of the auxiliary mechanism for organic fertilizer side throwing. Int J Agric & Biol Eng, 2025; 18(4): 157–169.